1998
DOI: 10.1111/j.1365-2796.1998.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of smoking, alcohol and physical activity with risk factors for coronary heart disease and diabetes risk in the first follow‐up cohort of the Heart Disease and Diabetes Risk Indicators in a Screened Cohort study (HDDRISC‐1)

Abstract: Godsland IF, . Associations of smoking, alcohol and physical activity with risk factors for coronary heart disease and diabetes in the first follow-up cohort of the Heart Disease and Diabetes Risk Indicators in a Screened Cohort study. J Intern Med 1998; 244: 33-41.Objectives. To investigate the associations between risk factors for cardiovascular disease and cigarette smoking, alcohol intake, and physical activity in a group of predominantly healthy men. Design. Cohort study with baseline characterisation, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…An association between increased parameters of inflammation and sympathetic overactivity was reported in both a healthy young population [14] and an elderly population without heart disease [15]. An animal study revealed that parasympathetic nervous system activity may have anti-inflammatory effects [16].…”
Section: Copd and Systemic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between increased parameters of inflammation and sympathetic overactivity was reported in both a healthy young population [14] and an elderly population without heart disease [15]. An animal study revealed that parasympathetic nervous system activity may have anti-inflammatory effects [16].…”
Section: Copd and Systemic Inflammationmentioning
confidence: 99%
“…Both COPD and chronic lung disease are associated with sympathetic nervous system activation (fig. 2) due to systemic inflammation [14,15,16], hypoxia [29], lower baroreflex sensitivity [37], inhibition of pulmonary stretch receptors [38], and elevated muscle sympathetic nerve activity [39]. Vascular stiffness was also reported to be elevated in COPD patients [37,40], and the lower baroreflex sensitivity due to vascular stiffness [37] may also result in augmented sympathetic nerve activity.…”
Section: Mechanism Of Cardiovascular Risk In Patients With Lung Diseasesmentioning
confidence: 99%
“…However, a characteristic of such diseases is that they can primarily be alleviated by lifestyle improvements [2,3,8,13,14,19,27,41,55]. The preventive management of metabolic syndromes presented by the third cholesterol management guidelines of the US [39], which defined metabolic syndromes and suggested clinical guidelines, emphasizes that strong lifestyle improvements will act as prevention and management strategies for primary and secondary diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report individuals who smoke demonstrate reduced insulin sensitivity compared with nonsmokers, 31,[38][39][40][41] whereas others report that current smoking is not associated with decreased insulin sensitivity, and, in some studies, may actually improve insulin sensitivity. 24,[42][43][44][45] Finally, although a large volume of research suggests that CRP is elevated in long-term smokers, 46-51 the mechanism of this effect is unclear. Unclear also is the effect of tobacco smoke exposure on inflammatory cytokines, with reports suggesting both an increase 48,52 and a decrease [53][54][55] in cytokines with smoking.…”
mentioning
confidence: 99%
“…57 A smoking history of at least 20 years carries with it the significant likelihood of established morbidity that may independently contribute to both inflammation and to the diagnosis of metabolic syndrome. 42,46,49 Metabolic syndrome is the outcome of many years of accumulating health risks. Although the characteristics of established disease are well recognized, the path of progression from health to disease, taken by young, generally healthy individuals exposed to varying risk factors, is unclear.…”
mentioning
confidence: 99%